TEORI BELAJAR POPULER UNTUK KEBERHASILAN PEMBELAJARAN - Fella Hanna Neisha; Neviyarni Suhaili; Herman Nirwana (Cahaya Ilmu Bangsa Institute, 2024)
Learning is a hot topic that can be discussed. The subjects of learning in schools are teachers and students. This article describes several learning methods that teachers can use in the learning process. The learning methods described in this article consist of four popular learning methods consisting of intelligent character education, self-directed learning, quantum learning and contextual learning. Efforts made to minimize monotonous learning are by understanding the theory of learning.